ANSWER :
The answer is :
![g(x)=-2x^2-10](https://img.qammunity.org/2023/formulas/mathematics/high-school/sd26an63m1be9ms0rvqev42wpzlfck3gsm.png)
EXPLANATION :
From the problem, we have :
![h(x)=-2x^2-5](https://img.qammunity.org/2023/formulas/mathematics/high-school/hwn28b1hgorf00w7e6unzkm4hyirb6tiqr.png)
h(x) is translated vertically by 5 units downward and it becomes the graph of a function g.
So g(x) = h(x) - 5
negative 5 denotes that h(x) is translated 5 units downward.
So that will be :
![\begin{gathered} g(x)=h(x)-5 \\ g(x)=(-2x^2-5)-5 \\ g(x)=-2x^2-10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/3k77t5bpzgtxtpgm7lk3ydu8oegxsqly4d.png)